Sweet Cherry (Prunus avium L.) Cracking during Development on the Tree and at Harvest: The Impact of Methyl Jasmonate on Four Different Growing Seasons - María Celeste Ruiz-Aracil; Juan Miguel Valverde; Jose Manuel Lorente-Mento; Alberto Carrión-Antolí; Salvador Castillo; Domingo Martínez-Romero; Fabián Guillén (Agriculture, 2023)
Rainfall occurring during the developmental stages of sweet cherries on the tree can lead to significant preharvest losses, primarily due to fruit cracking. Certain cultivars exhibit a higher susceptibility to such losses, particularly when persistent rains coincide with advanced phenological stages. The current study aims to investigate the efficacy of preharvest methyl jasmonate (MeJA) applications at harvest and during distinct developmental ripening stages in mitigating sweet cherry cracking at harvest and on-tree ripening. Preharvest foliar applications of 0.5 mM MeJA were applied across various sweet cherry cultivars, including ‘Prime Giant’, ‘Early Lory’, ‘Sweetheart’, and ‘Staccato’. By conducting this experiment over four growing seasons, we evaluated the impact of this natural elicitor on the cracking tolerance of these cultivars. The results of our analysis indicate that MeJA preharvest treatments effectively reduce fruit cracking, enhancing abiotic stress tolerance. Additionally, these treatments induce a general delay in fruit ripening on the tree across the examined cultivars. This delayed ripening effect is reflected in several quality parameters at harvest, such as the fruit firmness, external colour, total soluble solids, and total acidity. These parameters in the MeJA-treated fruit were delayed compared to the control fruit or remained unaffected for the total acidity. Conversely, the MeJA treatments delayed the accumulation of total polyphenols, exhibiting a minimal impact on reducing pedicel browning. The enhanced tolerance to cracking and delayed ripening attributed to the MeJA preharvest treatments could be helpful for plot management. Consequently, these MeJA-based preharvest treatments hold potential as valuable tools in adapting to climate change and mitigating abiotic stress in sweet cherry.